First-line treatment of nonsquamous NSCLC using gemcitabine: a retrospective study of real-life practice. (November 2016) - Kohutek, Filip; Stratena, Miroslava; Rosik, Andrej; Tamasova, Maria; Bystricky, Branislav
We present results of retrospective real-life data of nonsquamous lung cancer patients treated in first-line (platinum-based chemotherapy with gemcitabine without bevacizumab). 56 patients with satisfactory performance status for cytotoxic chemotherapy were treated in 2010–2014. Median progression-free survival was 6.48 months (95% CI: 4.44–9.48), time to progression was 10.19 months (95% CI: 7.59–12.19). Median overall survival was 10.8 months (95% CI: 6.72–14.52). Although our group of patients had higher proportion of elderly patients with somewhat limited performance status, progression-free survival rate was comparable to large registration studies. Overall survival, despite intervening comorbidities and subsequent limited use of second-line treatment was analogous to large gemcitabine/platinum Phase III studies in nonsquamous population. We believe our data represent real-life survival rates of unselected patients with advanced NSCLC of nonsquamous type from mostly rural catchment area.